2022
DOI: 10.1007/s11356-021-18442-x
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of air pollution on COVID-19 case fatality rate: a global analysis

Abstract: The coronavirus disease 2019 (COVID-19) pandemic is still rapidly spreading globally. To probe high-risk cities and the impacts of air pollution on public health, this study explores the relationship between the long-term average concentration of air pollution and the city-level case fatality rate (CFR) of COVID-19 globally. Then, geographically weighted regression (GWR) is applied to examine the spatial variability of the relationships. Six air pollution factors, including nitrogen dioxide (NO 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…Thus, COVID-19 CFRs are widely considered to be influenced by multidimensional factors. Previous studies have tried to explain cross-country variation in COVID-19 CFR using a variety of unidimensional factors such as population age structure[ 7 , 8 ], comorbidities [ 9 , 10 ], medical resources [ 11 ], environment [ 12 ], culture, and so on [ 13 ]. While these studies have found some associations, they have also ignored the important interaction effects of these factors on the risk of COVID-19 death within a single country.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, COVID-19 CFRs are widely considered to be influenced by multidimensional factors. Previous studies have tried to explain cross-country variation in COVID-19 CFR using a variety of unidimensional factors such as population age structure[ 7 , 8 ], comorbidities [ 9 , 10 ], medical resources [ 11 ], environment [ 12 ], culture, and so on [ 13 ]. While these studies have found some associations, they have also ignored the important interaction effects of these factors on the risk of COVID-19 death within a single country.…”
Section: Introductionmentioning
confidence: 99%
“…The risk of death from COVID-19 varies between countries, and case fatality rate (CFR) is an important indicator used to assess it. It is widely considered that the COVID-19 CFRs are affected by multidimensional factors, such as the SARS-CoV-2 variant infected ( 3 ), vaccination coverage ( 4 ), population age structure ( 5 , 6 ), health service ( 7 ), disease burden ( 8 , 9 ), environment ( 10 ), and so on ( 11 ). Of these, as the COVID-19 CFR is strongly associated with age, considering age structure when comparing CFR differences across countries is more helpful in minimizing potential bias ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies using statistical and computational techniques have shown that air pollution threatens human health and affects the spread of communicable diseases [ 4 , 5 ]. A large number of research results have also offered accumulated proof of the influence of pollutants in the air on the transmission of communicable diseases such as influenza, measles, COVID-19, and so on [ 6 9 ]. Therefore, it has been one of the most fun and significant topics to investigate the impact of pollutants in the air on the burst of communicable diseases [ 10 ].…”
Section: Introductionmentioning
confidence: 99%